2021
DOI: 10.3390/molecules26092518
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Strategies for Tissue Engineering in Regenerative Medicine: A Biofabrication and Biopolymer Perspective

Abstract: Tissue engineering is known to encompass multiple aspects of science, medicine and engineering. The development of systems which are able to promote the growth of new cells and tissue components are vital in the treatment of severe tissue injury and damage. This can be done through a variety of different biofabrication strategies including the use of hydrogels, 3D bioprinted scaffolds and nanotechnology. The incorporation of stem cells into these systems and the advantage of this is also discussed. Biopolymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 99 publications
0
31
0
Order By: Relevance
“…The creation of three-dimensional (3D) scaffolds is crucial in the field of tissue engineering. These scaffolds not only function as templates upon which new tissue can be produced but also need to be porous to ensure adequate transport of oxygen and nutrients [1]. Mechanical properties such as compressive strength and stiffness also dictate the success of a scaffold at its site of action, specifically in the regeneration of soft tissue such as cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of three-dimensional (3D) scaffolds is crucial in the field of tissue engineering. These scaffolds not only function as templates upon which new tissue can be produced but also need to be porous to ensure adequate transport of oxygen and nutrients [1]. Mechanical properties such as compressive strength and stiffness also dictate the success of a scaffold at its site of action, specifically in the regeneration of soft tissue such as cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Another biocompatible polymer with adhesive properties and low immunogenicity, widely used in dental applications, is based on gelatin [ 51 ]. It is hydrolyzed collagen investigated for application in tissue engineering [ 52 ]. Drug forms prepared with the use of gelatin have high hemostatic activity and significantly improve the process of healing/regenerating damaged tissues, including post-extraction wounds [ 51 , 53 , 54 ].…”
Section: Chemical Classification and Biological Activity Of Natural Dental Polymersmentioning
confidence: 99%
“…In some cases, they can even boost innate antibacterial properties of some of the commonly used biopolymers in these applications, like Mayerberger et al [ 68 ] observed. Chitosan has intrinsic antibacterial properties [ 69 ], which are further improved with the addition of MXenes. The group of Mayerberger demonstrated that a nanofibrous composite of CS/MXene significantly reduced bacteria viability compared with a pristine CS scaffold.…”
Section: Introductionmentioning
confidence: 99%